Isolation and characterization of lactic acid bacteria in fermented sweet corn (Zea mays l) as antibacterial - Rosario Trijuliamos Manalu; Amelia Febriani; S. Syamsinar (Bioscience, 2021)
Sweet corn (Zea mays L.) is a staple food that is known to produce Lactic Acid Bacteria (LAB) during the fermentation process, LAB is a probiotic bacterium that can produce antimicrobial components. This study aims to examine the characteristics and antibacterial activity of LAB sweet corn against Escherchia coli and Staphylococcus aureus.The study was conducted by isolating LAB from corn fermentation spontaneously which then tested the characteristics of the isolates obtained and tested for antibacterial activity. From the isolation results 3 isolates were obtained, namely FJM 1, FJM 2 and FJM 3 with morphological characteristics of rod-shaped and Gram-positive cells and biochemical test results; negative catalase, citrate, indole, motility, VP and positive TSIA. The results of antibacterial activity tests on E. coli were obtained respectively at 14.18 mm, 12.38 mm and 11.18 mm and S. aureus respectively at 13.05 mm, 11.12 mm and 10.35 mm. All three isolates had strong category antibacterial activity. Jagung manis (Zea mays L.) adalah makanan pokok yang diketahui menghasilkan Bakteri Asam Laktat (BAL) selama proses fermentasi, BAL merupakan suatu bakteri probiotik yang dapat menghasilkan komponen antimikroba. Penelitian ini bertujuan untuk menguji karakteristik dan aktivitas antibakteri BAL jagung manis terhadap Escherchia coli dan Staphylococcus aureus. Penelitian dilakukan dengan mengisolasi BAL dari fermentasi jagung secara spontan yang kemudian diuji karakteristik dari isolat yang didapatkan serta diuji aktivitas antibakterinya. Dari hasil isolasi didapatkan 3 isolat yaitu FJM 1, FJM 2 dan FJM 3 dengan karakteristik morfologi sel berbentuk batang dan Gram positif serta hasil uji biokimia; katalase, sitrat, indol, motilitas, Vp negatif dan TSIA positif. Hasil uji aktivitas antibakteri terhadap E. coli didapatkan berturut sebesar 14,18 mm, 12,38 mm dan 11,18 mm dan S. aureus berturut sebesar 13,05 mm, 11,12 mm dan 10,35 mm. Ketiga isolat memiliki aktivitas antibakteri kategori kuat.